1986
DOI: 10.1152/jappl.1986.61.4.1560
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin concentrations and blood gas tensions of free-diving Weddell seals

Abstract: Arterial blood gas tensions, pH, and hemoglobin concentrations were measured in four free-diving Weddell seals Leptonychotes weddelli. A microprocessor-controlled sampling system enabled us to obtain 24 single and 31 serial aortic blood samples. The arterial O2 tension (PaO2) at rest [78 +/- 13 (SD) Torr] increased with diving compression to a maximum measured value of 232 Torr and then rapidly decreased to 25-35 Torr. The lowest diving PaO2 we measured was 18 Torr just before the seal surfaced from a 27-min d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
105
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(114 citation statements)
references
References 0 publications
7
105
2
Order By: Relevance
“…Although the spleen has long been suspected as the source of the RBCs released during diving, the rate of splenic contraction has presented an apparent contradiction to the gradual divinginduced rise in Hct (2,6). In this study, maximal Hct occurred after the 7-min dive had concluded, whereas the spleen had released the majority of its RBCs by dive min 2.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Although the spleen has long been suspected as the source of the RBCs released during diving, the rate of splenic contraction has presented an apparent contradiction to the gradual divinginduced rise in Hct (2,6). In this study, maximal Hct occurred after the 7-min dive had concluded, whereas the spleen had released the majority of its RBCs by dive min 2.…”
Section: Discussionmentioning
confidence: 51%
“…hocid seals exhibit a higher hematocrit (Hct) during apnea and diving than during periods of eupneic respiration (1)(2)(3)(4). This variation in red cell mass indicates that seals have some method of sequestering red cells during nonapneic events.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that these organisms have higher than typical vertebrate levels of blood volume, Hb concentrations, hematocrit, and myoglobin concentrations (Ridgway and Johnston, 1966;Bryden and Lim, 1969;Elsner, 1969;Kooyman et al, 1980;Vogl and Fisher, 1982;Cornell, 1983;Duffield, Ridgway and Cornell, 1983;Snyder, 1983;Kanwisher and Ridgway, 1983;Ridgway et al, 1984;Qvist et al, 1986;Hedrick, Duffield and Cornell, 1986;Kooyman, 1986).…”
Section: Ecotypes Of Bottlenose Dolphinsmentioning
confidence: 99%